2021
DOI: 10.1021/acsami.1c13245
|View full text |Cite
|
Sign up to set email alerts
|

Delicately Controlled Polymer Orientation for High-Performance Non-Fullerene Solar Cells with Halogen-Free Solvent Processing

Abstract: Molecular orientation in polymer solar cells (PSCs) is a critical subject of investigation that promotes the quality of bulk heterojunction morphology and power conversion efficiency (PCE). Herein, the intrinsic polymer orientation transition can be found upon delicate control over the branching point position of the irregular alkoxy side chain in difluoroquinoxaline−thiophene-based conjugated polymers. Three polymers with branching points at the third, fourth, and fifth positions away from the backbone were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Previous reports have confirmed that relative to alkyl group, the siloxane terminal possesses lower surface energy property. Although the contents of the siloxane terminal in PQSi505, PQSi705, and PQSi905 are the same (5 %), the result suggests a longer linker in the polymer would result in a lower surface energy [6c,12] . In this regard, the siloxane terminal group is a powerful modulator to regulate surface property.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous reports have confirmed that relative to alkyl group, the siloxane terminal possesses lower surface energy property. Although the contents of the siloxane terminal in PQSi505, PQSi705, and PQSi905 are the same (5 %), the result suggests a longer linker in the polymer would result in a lower surface energy [6c,12] . In this regard, the siloxane terminal group is a powerful modulator to regulate surface property.…”
Section: Resultsmentioning
confidence: 97%
“…Our result indicates that the slight branching position change of siloxane‐terminated group can greatly influence the orientation and crystallinity features. Thus, the siloxane pendant can be regarded as a powerful hybrid functional group, considering the extremely low molar content of the siloxane‐terminated side chain (5 %) in the polymers [5a,6c,13] . Generally, conjugated polymers with high crystallinity would exhibit outstanding charge transport.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate pre-aggregation is recognized as a prerequisite for achieving high-quality active layer films. [67][68][69] Cao et al 70 revealed that the polymer donor PTzBI and acceptor N2200 exhibited strong intrinsic pre-aggregation in 2-methyltetrahydrofuran (Me-THF) solvent. Such pre-aggregation contributes to the formation of interpenetrating network structures with small domains and high domain purity (Fig.…”
Section: Pre-aggregation Strategymentioning
confidence: 99%
“…Several other nonfullerene acceptors such as tetrachlorinated IT-4Cl, 97 perylene bisimide-based SdiPBI-Se, 98 and fused dithienothiophen[3,2-b]-pyrrolobenzotriazole-(BTA-core-) based Y14 99 were also capable of influencing the packing orientation of donor polymers. The extended conjugation of such acceptors significantly enhanced their interaction with conjugated polymers (donor), efficiently tuning the polymer packing orientation.…”
Section: Other Factorsmentioning
confidence: 99%